Paradoxical response as a cervical lymph node enlargement after termination of anti-tuberculosis treatment in a patient with pulmonary tuberculosis - Hye-Rim Kang; Ho Young Lee; Mi-Yeong Kim; Young Min Lee; Soo Jin Jung; Hyun-Kyung Lee; Si Hyeong Lee; Yunmi Kim (Kosin Medical Journal, 2016)
Abstract A paradoxical response is not uncommon in non-HIV-infected patients, particularly those with extra-pulmonary tuberculosis. It is defined as the radiological and clinical worsening of a previous lesion or the development of new lesion during anti-tuberculosis therapy. The paradoxical response has been attributed to host immunologic reactions, such as a delayed hypersensitivity or a response to mycobacterial antigens. In most reports of paradoxical response, these responses occurred in the same location as a previous lesion. In this patient with pulmonary tuberculosis, cervical lymph node enlargement occurred as a paradoxical response after the completion of anti-tuberculosis treatment. Although the new lesion developed in another location, it could be considered as a paradoxical response based on the negative culture result of acid fast bacilli from the new lesion and drug sensitivity result from initial bronchoalveolar lavage specimen. Therefore we were able to decide on the termination of unnecessary anti-tuberculous treatment. Based on our case, we can conclude that paradoxical response can occur after the termination of anti-tuberculosis therapy even in new site.